Polymorphism of common hazel crown in natural population - S. G. Biganova; Yu. I. Sukhorukikh; T. A. Isushcheva (Новые технологии)
On the basis of randomized selection of common hazel (Corylus Avellana L.) in the natural population of the North-West Caucasus, crown polymorphism has been studied by shape, diameter, height, density and diameter of the bush base. Plants grow at heights of 250-1,500 m above the sea level. Classification has been carried out on the basis of the well-known methodology for the pomological description of varieties. 450 fruiting rames of various ages have been examined so far. Data processing has been performed using the «Stadia» computer program.  It has been established that more than 74% of plants in the population have a rare and dense crown. Bushes of medium density are represented by one quarter. The proportion of individuals with a weeping crown shape, which is of the greatest value for decorative purposes, was found in 0.22 % of cases. The main part of the plants has a shoot distribution diameter at the base of the bush from 0.10 m to 0.5 m, they account for 60.22 %. The diameter of the hazel crowns in the population vary between 1-12 m, and has a significant coefficient of variation of 42.13 %. Fruiting plants have a height ranging from 2 to 15 m, coefficient of variation of 40.33 %. The presence of individuals with a height of up to 3 m and more than 12 m suggests the possibility of selection of both undersized and overgrown forms.